Pengenalan dan Pemberian Terapi Komplementer Akupuntur Pada Masyarakat Desa Wonosari Kecamatan Penajam Paser Utara Kalimantan Timur - Risna Agustina; Chaidir Masyhuri Majiding; Wisnu Cahyo Prabowo; Raisa Fadilla; Norna Marliza; Satrianingsih Satrianingsih; Delfia Shamara; Yansur Yansur; Abdul Rahim (Universitas Pahlawan Tuanku Tambusai, 2023)
Complementary medicine is a type of treatment that can be used as an option by the community in the midst of the existence of conventional medicine, but in fact there are still many people who do not really know and experience complementary medicine in the firsthand. The purpose of this community service is to provide an introduction, understanding, and experience to the people of Wonosari Village regarding complementary therapies, especially acupuncture as way to improve health status. This community service consists of four activities: education on various complementary therapies, introduction and administration of acupuncture therapy, health checks and treatment education, and also education and mental health examinations. Based on the results of the evaluation, all participants rated this service activity were very useful, the participants became more familiar with the types of complementary therapies, especially being able to feel the changes after getting acupuncture therapy directly. Participants were also very happy and greatly helped by the existence of health checks and medical education as well as mental health as part of the supporting activities in this community service activity.